Real Power Loss Minimization and Voltage Stability Enhancement by Hybridization of Eagle Strategy with Particle Swarm Optimization Algorithm - Lenin, K. (Journal of the Institute of Engineering, 2018)
In this paper, Hybridization of Eagle Strategy (ES) with Particle Swarm Optimization is proposed to solve the optimal reactive power dispatch Problem. Proposed hybridization of Eagle Strategy with Particle Swarm Optimization (EPSO) enhances the search in rigorous mode. Eagle strategy has been instigating by the foraging behaviour of golden eagles. This stratagem has two important parameters: arbitrary search and exhaustive chase. At first it explores the search space globally, and then in the second case the strategy makes an intensive local search with using an effective local optimizer method. So, Particle Swarm Optimization has been enhanced using ES and employed to solve reactive power optimization problem. In order to appraise the efficiency of the projected EPSO algorithm, it has been tested in standard IEEE 30 bus system and compared other reported algorithms. Results show’s that EPSO algorithm is more efficient in plummeting the real power loss and voltage index also enhanced. Journal of the Institute of Engineering, 2018, 14(1): 22-34